2009
DOI: 10.1159/000232927
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modafinil on Subjective Fatigue in Multiple Sclerosis and Stroke Patients

Abstract: Background: Modafinil has anecdotal response to neurological fatigue, but such an effect may depend on the type and location of cerebral impairment. Objectives: It was the aim of this study to compare fatigue observed in different neurological pathologies, to evaluate the tolerability to modafinil, and to describe changes in subjective fatigue. Methods: We enrolled 14 brainstem or diencephalic stroke (BDS) patients, 9 cortical stroke (CS) patients and 17 multiple sclerosis (MS) patients. The Fatigue Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 55 publications
0
35
0
3
Order By: Relevance
“…14 Several small studies have found that treatment with modafinil, a wake-promoting agent, improved symptoms of MS fatigue, although in a larger randomized controlled trial there was no difference. [15][16][17] These studies did not use objective measures of alertness. Beyond these pharmaceutical studies, little research has been conducted into whether poor sleep and decreased alertness are major determinants of MS fatigue.…”
Section: Original Articlementioning
confidence: 99%
“…14 Several small studies have found that treatment with modafinil, a wake-promoting agent, improved symptoms of MS fatigue, although in a larger randomized controlled trial there was no difference. [15][16][17] These studies did not use objective measures of alertness. Beyond these pharmaceutical studies, little research has been conducted into whether poor sleep and decreased alertness are major determinants of MS fatigue.…”
Section: Original Articlementioning
confidence: 99%
“…The earlier modafinil trial in patients with stroke had a dropout rate because of side effects of 25% despite a lower dosage. 19 Therefore, our use of the maximum allowed dose of 400 mg in patients aged <65 years does not seem to have had influenced the amount of adverse effects, but adverse events seem to be a consistent problem.…”
Section: Discussionmentioning
confidence: 86%
“…Investigators found a positive effect on patients with brain stem and diencephalic strokes, but not on patients with cortical stroke. 19 Because of different end points and the uncontrolled design, the effect size cannot be directly compared with our trial. Because of the few included patients in our trial, it did not make sense to compare patients with, for example, brain stem and cortical strokes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…203 Modafinil was studied in 23 young patients (aged <70 years) with mild strokes 12 to 48 months from the acute event; the study was limited by a high dropout rate, and treatment was found to be effective only in a subgroup of stroke patients. 204 Amantadine and methylphenidate have been used to treat cancer fatigue or fatigue in other neurological conditions 205 but have not been studied for fatigue in the stroke population.…”
Section: Fatiguementioning
confidence: 99%